2005
DOI: 10.1099/mic.0.28215-0
|View full text |Cite
|
Sign up to set email alerts
|

The fluorene catabolic linear plasmid in Terrabacter sp. strain DBF63 carries the β-ketoadipate pathway genes, pcaRHGBDCFIJ, also found in proteobacteria

Abstract: The fluorene catabolic linear plasmid in Terrabacter sp. strain DBF63 carries the b-ketoadipate pathway genes, pcaRHGBDCFIJ, also found in proteobacteria Terrabacter sp. strain DBF63 is capable of degrading fluorene (FN) to tricarboxylic acid cycle intermediates via phthalate and protocatechuate. Genes were identified for the protocatechuate branch of the b-ketoadipate pathway (pcaR, pcaHGBDCFIJ) by sequence analysis of a 70 kb DNA region of the FN-catabolic linear plasmid pDBF1. RT-PCR analysis of RNA from DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…After the RT reaction, quantitative real-time PCR with SYBR GREEN PCR Master Mix (Applied Biosystems, Foster City, CA) was performed using the synthesized cDNA as a template on the ABI7700 sequence detection system (Applied Biosystems). The copy number of each mRNA was determined by a standard curve using a series of known concentrations of the target sequence according to the method of Habe et al (10). For normalization, 16S rRNA of KA1 was used as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…After the RT reaction, quantitative real-time PCR with SYBR GREEN PCR Master Mix (Applied Biosystems, Foster City, CA) was performed using the synthesized cDNA as a template on the ABI7700 sequence detection system (Applied Biosystems). The copy number of each mRNA was determined by a standard curve using a series of known concentrations of the target sequence according to the method of Habe et al (10). For normalization, 16S rRNA of KA1 was used as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…In DBF63, the DFDO is thought to be composed of a multicomponent system with a terminal oxygenase, ferredoxin, and ferredoxin reductase, although the specific ferredoxin reductase has not been identified in the DBF63 genome (60). The dbf genes are localized on a linear plasmid pDBF1 in DBF63 clustered with other fluorene-catabolic (fln) genes, phthalate-catabolic (pht) genes, and protocatechuate-catabolic (pca) genes, and their products can convert fluorene into tricarboxylic acid cycle intermediates (22,23,25). From the pCAR3 sequence, we found a gene encoding a candidate ferredoxin component of the DFDO; the product of ORF243 showed 33% identity with CumA3 identified in P. fluorescens IP01 (24), and it had a putative Rieske-type [2Fe-2S] binding motif (data not shown).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Third, the gene products might function as degrading enzymes for other compounds not used in the present study. As for phthalate and protocatechuate, one of the intermediate compounds of dibenzofuran or fluorene (22,23,25,42), both strains KA1 and Anthranilate…”
Section: Downloaded Frommentioning
confidence: 99%
“…In this case, studies have shown that the function of a gene can often be deduced from the gene organization or arrangement (14,15,52,55). We analyzed the genomic contexts to search missing ORFs for which functional evidence is lacking.…”
Section: Pyrene Induction Experimentmentioning
confidence: 99%